2020
DOI: 10.1002/acm2.12902
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning of a 1.5T Elekta Unity MR‐linac: A single institution experience

Abstract: MR image-guided radiotherapy has the potential to improve patient care, but integration of an MRI scanner with a linear accelerator adds complexity to the commissioning process. This work describes a single institution experience of commissioning an Elekta Unity MR-linac, including mechanical testing, MRI scanner commissioning, and dosimetric validation. Mechanical testing included multileaf collimator (MLC) positional accuracy, measurement of radiation isocenter diameter, and MR-to-MV coincidence. Key MRI tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
112
5
11

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(137 citation statements)
references
References 39 publications
9
112
5
11
Order By: Relevance
“…For the 7 MV FFF beam quality, the simulated beam quality specifier is in excellent agreement with experimental results that can be found in the literature [12] , [23] . De Prez et al [12] found and Snyder et al [23] published a value of . In contrast, the results of this work do not agree with the Monte Carlo simulated values of other authors [9] , [10] .…”
Section: Discussionsupporting
confidence: 85%
“…For the 7 MV FFF beam quality, the simulated beam quality specifier is in excellent agreement with experimental results that can be found in the literature [12] , [23] . De Prez et al [12] found and Snyder et al [23] published a value of . In contrast, the results of this work do not agree with the Monte Carlo simulated values of other authors [9] , [10] .…”
Section: Discussionsupporting
confidence: 85%
“…In this paper we have described our initial findings with respect to image quality using a prototype patient rotation system for a high-field in-line MRI-Linac. With the PRS in-situ, geometric distortion was within 1.6 ppm, which could likely be accounted for with active shimming, and is consistent with commercial MRI-Linac systems for a DSV of 20 cm [13,14]. A previous study by Shan et al quantified the B0-field inhomogeneity of the MRI-Linac used in this study, using the same B0 mapping approach [15].…”
Section: Discussionsupporting
confidence: 78%
“…Due to the design of the Unity MR-linac, the ArcCheck phantom is first placed on the QA platform and translated into the bore. A CT scan of the ArcCheck was imported into the Monaco treatment planning system(TPS) and the relative electron densities were determined as described by Snyder et al14,15 The alignment of the ArcCheck phantom utilizes a custom QA platform since the Unity MR-linac only has a sagittal laser, which is insufficient to properly align the phantom by itself. As a result, the alignment reproducibility is dependent on the consistency of how the ArcCheck phantom and platform are setup on the treatment couch.…”
mentioning
confidence: 99%